PENINGKATAN JOB PERFORMANCE KARYAWAN FRONTLINER PERBANKAN JAWA TIMUR MELALUI ORGANIZATIONAL LEARNING DAN TRANSFORMATIONAL LEADERSHIP - Pranindy, Jihan Salsabilla Ardine; Hardianto, Alviana Ajeng; Agustina, Tri Siwi (PT Naureen Digital Education, 2024)
The purpose of this study is to investigate the influence of Organizational learning culture and Transformational leadership on Job performance through the mediating role of Job satisfaction in the banking industry. The method used is a quantitative approach with Structural Equation Modeling-Partial Least Square (SEM-PLS) to analyze data from frontliner employees in the banking sector in East Java. The results showed that Organizational learning culture and Transformational leadership have a positive and significant effect on Employee Performance and Job satisfaction. Job satisfaction is also proven to mediate the effect of Organizational learning culture and Transformational leadership on Job performance. The limitation of this study lies in a sample limited to frontliner employees in the banking sector in East Java, which may not represent the entire banking industry. Suggestions for future research are to explore additional factors that may influence the relationship between Organizational learning culture, Transformational leadership, Job satisfaction, and Job performance, and to expand the sample to various sectors and geographical areas